2022
DOI: 10.3390/jof8101002
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective Effects of Two Ganoderma Species Methanolic Extracts in an In Vitro Model of Cisplatin Induced Tubulotoxicity

Abstract: Although cisplatin is used as a first-line therapy in many cancers, its nephrotoxicity remains a real problem. Acute kidney injuries induced by cisplatin can cause proximal tubular necrosis, possibly leading to interstitial fibrosis, chronic dysfunction, and finally to a cessation of chemotherapy. There are only a few nephroprotective actions that can help reduce cisplatin nephrotoxicity. This study aims to identify new prophylactic properties with respect to medicinal mushrooms. Among five Ganoderma species, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…This result was deemed statistically significant [ 84 ]. The presence of phytochemicals in two species of Ganoderma mushroom was investigated [ 112 ]. Upon analyzing the methanolic extract, it was observed that the presence of carbohydrates, terpenes, and a small quantity of saponins was evident [ 112 ].…”
Section: Phytochemical Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was deemed statistically significant [ 84 ]. The presence of phytochemicals in two species of Ganoderma mushroom was investigated [ 112 ]. Upon analyzing the methanolic extract, it was observed that the presence of carbohydrates, terpenes, and a small quantity of saponins was evident [ 112 ].…”
Section: Phytochemical Investigationsmentioning
confidence: 99%
“…Upon analyzing the methanolic extract, it was observed that the presence of carbohydrates, terpenes, and a small quantity of saponins was evident [ 112 ]. However, no alkaloids or flavonoids were detected [ 112 ]. Qualitative and quantitative methods were employed to assess the phytochemical content of the H. erinaceus mushroom, revealing a substantial quantity of phenolics and high levels of protein and nitrogen [ 82 ].…”
Section: Phytochemical Investigationsmentioning
confidence: 99%